CLINICAL AND LABORATORY RESULTS OF THE USE OF PURE PROGESTIN CONTRACEPTION IN WOMEN AFTER CESAREAN SECTION (Archive of Conferences, 2020)
To analyze the acceptability, side effects, and complications of the reversible method of contraception (PPC) prescribed in the postpartum period